A velocity program using the Kanade–Lucas–Tomasi feature‐tracking algorithm with demonstration for pressure and electroosmosis conditions. Issue 7 (4th February 2022) - Devasagayam, Jasen; Bosma, Rick; Collier, Christopher M.
Abstract: Investigating microfluidic flow profiles is of interest in the microfluidics field for the determination of various characteristics of a lab‐on‐a‐chip system. Microparticle tracking velocimetry uses computational methods upon recording video footage of microfluidic flow to ultimately visualize motion within a microfluidic system across all frames of a video. Current methods are computationally expensive or require extensive instrumentation. A computational method suited to microparticle tracking applications is the robust Kanade–Lucas–Tomasi (KLT) feature‐tracking algorithm. This work explores a microparticle tracking velocimetry program using the KLT feature‐tracking algorithm. The developed program is demonstrated using pressure‐driven and EOF and compared with the respective mathematical fluid flow models. An electrostatics analysis of EOF conditions is performed in the development of the mathematical using a Poisson's Equation solver. This analysis is used to quantify the zeta potential of the electroosmotic system. Overall, the KLT feature‐tracking algorithm presented in this work proved to be highly reliable and computationally efficient for investigations of pressure‐driven and EOF in a microfluidic system.